1989
DOI: 10.1111/j.1530-0277.1989.tb00284.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Effects of Long‐Term Ethanol Consumption on the Heart and Liver of the Rat

Abstract: Alterations in heart and liver metabolism were determined periodically in Sprague-Dawley rats pair-fed a liquid diet (ethanol, 36% of calories) for times as long as 1 year. In liver mitochondria the rate of ATP synthesis was lowered significantly after ethanol administration for 1 month and longer feeding periods. In liver microsomes from ethanol-fed animals, ethanol oxidation and aniline hydroxylation increased 1.5- and 3.5-fold, respectively, after 1 month and remained elevated at the longer feeding interval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

1990
1990
2004
2004

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…Ethanol treatment causes tissue-specific changes in mitochondrial morphology and membrane physical properties, including effects on mitochondrial inner membrane phospholipids and alterations in the activity and kinetic properties of several mitochondrial enzymes (reviewed in [2,4]). Mitochondrially encoded subunits of electron-transport-chain complexes and ATP synthase are specifically affected, resulting in a decrease by 30-50 % in the activity of NADH dehydrogenase, cytochrome bc " complex, cytochrome oxidase and ATP synthase [1,6,24,26]. These changes in mitochondrial characteristics occur in liver over a period of 3-5 weeks of ethanol feeding by the LieberDeCarli protocol [14] and may be more extensive with other more invasive ethanol-feeding protocols.…”
Section: Discussionmentioning
confidence: 99%
“…Ethanol treatment causes tissue-specific changes in mitochondrial morphology and membrane physical properties, including effects on mitochondrial inner membrane phospholipids and alterations in the activity and kinetic properties of several mitochondrial enzymes (reviewed in [2,4]). Mitochondrially encoded subunits of electron-transport-chain complexes and ATP synthase are specifically affected, resulting in a decrease by 30-50 % in the activity of NADH dehydrogenase, cytochrome bc " complex, cytochrome oxidase and ATP synthase [1,6,24,26]. These changes in mitochondrial characteristics occur in liver over a period of 3-5 weeks of ethanol feeding by the LieberDeCarli protocol [14] and may be more extensive with other more invasive ethanol-feeding protocols.…”
Section: Discussionmentioning
confidence: 99%
“…41,42 In rats, the later stages of alcohol-dependent hepatotoxicity are associated with a decrease in the activity of the major proteins of oxidative phosphorylation. 18,43 The effects of alcohol on liver mitochondrial function in mice have not been re- Data represent mean Ϯ SEM for 6 pairs of wild-type mice on ethanol-containing diet (WT ETOH) or control diet (WT) and iNOS Ϫ/Ϫ mice on ethanol-containing diet (iNOS Ϫ/Ϫ ETOH) or control diet (iNOS Ϫ/Ϫ ).…”
Section: Discussionmentioning
confidence: 99%
“…31,32 These include structurally deformed and swollen organelles with changes in physical properties of the membrane and a decrease in the activity of respiratory complexes that contain mitochondrially encoded polypeptides. 31,33 In this study, these data were confirmed with chronic ethanol feeding resulting in a significant decrease in oxygen consumption, in the presence of complex I, II, or IV substrates. 34 Ethanol consumption is known to increase NO levels through the enhanced activity of inducible NO synthase.…”
Section: Discussionmentioning
confidence: 99%